PENGARUH NET PROFIT MARGIN, CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP FINANCIAL DISTRESS PADA PT GARUDA INDONESIA TBK (GIAA) TAHUN 2013-2022 - Faisal, Ahmad Ajrul; Yusran Daeng Matta (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of net profit margin, current ratio and debt to equity ratio on financial distress at PT Garuda Indonesia Tbk (GIAA) in 2013-2022. The research technique used is descriptive analysis and multiple linear regression using SPSS. The research results show that partially the net profit margin has a significant influence on financial distress with a probability value of 0.0010, <05. The current ratio partially has a significant influence on financial distress with a probability value of 0.003 <0.05 and the debt to equity ratio partially does not have a significant influence on financial distress with a probability value of 0.829 > 0.05. Meanwhile, simultaneously net profit margin, current ratio and debt to equity ratio influence financial distress with a probability value of 0.0010, <0,05